Effect of remote ischemic preconditioning on perioperative neurocognitive disorder in elderly patients undergoing major surgery and associated genetic variant analysis: a randomized clinical trial - Feifei Xu; Tingting Liu; Huiqing Liu; Jiao Deng; Shan He; Zhihong Lu; Haopeng Zhang; Hailong Dong (Perioperative Medicine)
Abstract Objective To investigate whether remote ischemic preconditioning (RIPC) could reduce the incidence of perioperative neurocognitive disorder (PND) in elderly patients undergoing major surgery (> 2 h), to assess the potential of myeloid differentiation factor 2 (MD2) and cystatin C as biomarkers and to identify key genetic variants associated with PND. Methods From August 2020, 250 patients scheduled for major surgeries under general anesthesia were screened and 120 patients were randomly assigned to the control group or the RIPC group. After anesthesia induction, patients in the RIPC group received a blood pressure cuff around their right upper limb, which was pressurized to 200 mmHg to induce ischemia, whereas the cuff in the control group was pressurized to only 60 mmHg. A total of five cycles were repeated with ischemia for five minutes and reperfusion for five minutes. Six neurological tests were performed before and after the surgery to assess the incidence of PND. Serum levels of myeloid differentiation factor 2 (MD2) and Cystatin C and PND-associated single nucleotide polymorphisms were analyzed by ELISA and whole genome sequencing, respectively. This study adhered to CONSORT research guidelines. Results In the RIPC group, the incidence of PND (44%) was comparable to that in the control group (44%, P = 0.982). There was no significant difference in the concentrations of MD2 or cystatin C between the NPND and PND groups. A total of 3877 mutated genes were exclusively identified in PND patients. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that these mutated genes are enriched in synapse function. Notably, a Shank3 variant (SNP rs4824145) was included. Conclusions RIPC had little effect on the incidence of PND in elderly patients who underwent major surgery (> 2 h). MD2 and cystatin C were unable to predict the occurrence of PND. Patients harboring rs4824145 in the Shank3 gene may be more susceptible to PND. Trial registration. Chinese Clinical Trial Registry (ChiCTR2000035020(07/28/2020)).